Response of leaf and soil C, N and P stoichiometry in different Pinus massoniana forest types to slope aspect in the Dabie mountains region of North subtropical, China - Qin, Juan; Liu, Ye; Bi, Qingkang; Chen, Ziqi; Zhang, Bowen (Frontiers in Environmental Science, 2023)
Changes in slope aspect have important effects on the C, N and P nutrient contents and stoichiometric characteristics of plants and soils. As an important forest type in the subtropical region, Pinus massoniana forests play an important role in the restoration and development of forest ecosystems. In this study, the effect of slope aspect on the C, N and P contents and stoichiometry of leaves and soils of four P. massoniana forest types (i.e., pure P. massoniana forest (PF), P. massoniana-Liquidambar formosana mixed forest (PLM), P. massoniana -Platycarya strobilacea mixed forest (PPM), and P. massoniana-Quercus acutissima mixed forest (PQM)) in north subtropical region of China were studied. The results showed that slope aspect had significant effects on soil C, N and P contents, leaf N content (LNC), soil C:P and N:P ratios, and leaf C:N and N:P ratios in four P. massoniana forests. SOC, STN and STP contents differed significantly on the two slopes, with the three mixed forests having higher contents on the sunny slope than on the shady slope. Among the four forest types, the SOC, STN and STP contents of PQM were the highest on both slopes, and their soil C:P and N:P ratios were all the highest on the sunny slope. The LNC and leaf N:P ratios were higher on shady slope than on sunny slope, while the leaf C:N ratio was higher on sunny slope than on shady slope. At the species level, leaf N content and N:P ratio in the three deciduous species were higher than in the evergreen species of P. massoniana, while leaf C content and C:N ratio were lower than in P. massoniana. The interaction between slope aspect and forest type caused a certain range of fluctuations in stoichiometry of the four forest types, but the overall ecological stoichiometry remained stable, and plant growth of the four forest types in the study area was limited by N. Slope-induced changes in soil nutrient content of the four P. massoniana forest types directly affect leaf C:N:P stoichiometry, and soil N and P contents are key factors affecting leaf stoichiometry, especially soil P content.